Pengaruh Bermain Papan Titian Terhadap Keseimbangan Anak Usia 5-6 Tahun - Surya, Putra Areza; , Agus Widodo, S.Fis., M.Fis (2016)
Background: Early childhood is children aged 0-6 years which at this age is called the golden age because at this time the potential to train and develop the various aspects of developments owned subsidiary. Approximately 80% of children who have developmental disorders also have difficulty in regulating body balance (Hildayani, 2008). In early childhood, body balance owned still not stable, but the balance need to carry out their activities of daily living (Yuliani, 2009). According Moeslichatoen (2004), play can be useful to improve the balance. In the play necessary to have the means to support that goal of the game can be achieved. One of them is to train the body balance with playing balance beam. Objective: To determine the effect of playing balance beam for children aged 5-6 years. Methods: The study of this research is quasi experiment. Design research is a pre and post test design with control group compared between the two groups, the treatment group were given exercise with playing balance beam 3 times a week for 4 weeks. Measuring tool balance using Timed Up & Go Test. Data were analyzed using the Wilcoxon signed rank to test the influence and Man Whitney to test different influences. Results: There was an effect of playing balance beam on the increase in the balance of children aged 5-6 years after the statistical test using Wilcoxon test showed a p-value of 0.001 in the treatment group and the control group getting the p-value of 0.004. While the influence of different test with man Whitney test showed a p-value of 0.008. Conclusion: There is an effect playing balance beam on the increase in the balance of children aged 5-6 years.